The Functional Movement Screen for Injury Prediction in Male Amateur Football / Der Functional Movement Screen zur Verletzungsvorhersage im Männer-Amateurfußball - Schroeder J; Wellmann K; Stein D; BraumannKM (Deutsche Zeitschrift für Sportmedizin)
Despite various research approaches,there is still conflicting evidence as to the worthiness of injury prediction tools in football. This study was aiming at investigating correlations between injuries of amateur male football players and the results of a Functional Movement Screen (FMS). Using an observational design, ten amateur teams of the fifth and sixth division (Deutscher Fuball-Bund) were examined by means of FMS scores prior to a tenweek off- and main- season observation period (July to September 2013). The assessment included injuries and football exposure times during training and competition. Injury was defined as concerning the lower limb, and as non-contact with time loss of at least three days. After a drop-out of 56% (125 out of 221), 96 players could be analysed. We calculated a total exposure time of 1.770 hours (competition 289 h, training 1,481 h). We observed 10 injury incidents concerning 8 players, occurring exclusively during training. The according incidence was 6.8 injuries per 1.000 training hours. There were no significantdifferences between injured and uninjured players neither for any FMS item nor for the total score except for the hurdle step (Z=-2.059; p=0.040). Only the ratings for the hurdle step task and the injury state were correlated significantly (rpbis=0.209; p=0.041). Even if taking into account some experimental limitations, we conclude that the FMS does not allow a valid injury prediction in the field of amateur male football players.KEY WORDS: Football, Functional Movement Screen, Injury Prediction